Development of halal plant-based hydrocolloids encapsulation for targeted delivery of bovine serum albumin - Mohamed, Hajaratul Najwa (2015)
Advances in biotechnology over the past few years have driven the production of various clinically useful protein and peptides. Till recent, parenteral route (injection) is the most common way for administering protein drugs. However, the patient compliance with injection regimens is very poor, particularly for disease like diabetes. Thus, oral route remains as the most preferable route to deliver protein drugs due to ease of administration. However, administration of protein and peptide drug through oral route is quite challenging in terms of controlled delivery, targeting formulations and controlled manner. One way to overcome this problem is by using encapsulation technique or incorporating the protein into microcapsule made of biodegradable polymers. The potential of using encapsulation method to develop controlled release matrices for protein delivery during passing through the gastrointestinal tract was investigated in this study. Konjac glucomannan and gum Arabic were chosen as the potential polysaccharides to be combined with sodium alginate as encapsulating matrices and bovine serum albumin (BSA) as model protein. The study was accomplished through the following approaches: 1) optimization of encapsulating matrices to produce controlledrelease formulation and improve encapsulation yield; 2) determination of protein release activities based on swelling rate (%) and in-vitro release during exposure to simulated gastric (SGF) and intestinal fluid (SIF); 3) determination of protein-polysaccharide interaction within the beads and bead morphology by using Fourier-Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy, respectively. Statistical modeling based on the Face Centered Central Composite Design (FCCD) was employed for the optimization of encapsulating matrices. The optimum concentration for alginatekonjac glucomannan was predicted at 4% (w/v) and 0.6% (w/v), respectively. Whereas, in the case of alginate-gum Arabic, combination of alginate at concentration 3% (w/v) and 2% (w/v) of gum Arabic was predicted to produce optimum responses. Through verification step, experimental data of alginate-konjac glucomannan and alginate-gum Arabic remained close value to the predicted value with low error for all the response. IR spectra of alginate-konjac glucomannan beads showed that electrostatic interaction and hydrogen binding exist between alginate and konjac glucomannan. In addition,significant characters of BSA were observed in IR spectrum which suggesting there was no interaction between the protein (BSA) and the polymer used (alginate and konjac glucomannan). In the case of alginate-gum Arabic beads, there was also no interaction between BSA and encapsulating matrices (alginate and gum Arabic). The SEM photograph of these beads showed spherical shape with a rough surface. Cracks and wrinkles also were seen on the beads surface which might occur during drying process. The performances of optimized alginate-konjac glucomannan and alginate-gum Arabic beads as sustained-release beads were determined. Five groups encapsulating matrices were evaluated (1: optimized alginate-konjac glucomannan, 2: optimized alginate-gum Arabic, 3: alginate-hydroxypropyl methylcellulose (HPMC), 4: alginate alone, 5: free protein). Low protein encapsulation efficiency was observed in group 4. On the other hand, group 2 showed the highest protein encapsulation efficiency. Slow swelling rate was observed during exposure to acidic medium (SGF) by groups 1 and 2 while groups 3 and 4 has demonstrated advanced swelling in 2h of exposure. The releases of protein occur when the beads disintegrate and these were observed through the release activity analysis. Positive performance in releasing protein into intestinal region was shown by groups 1, 2 and 3. The in vitro dissolution of these beads showed prolonged release of BSA for almost 4 h. Encapsulations of both konjac glucomannan and gum Arabic with alginate combination have successfully improved the survival and protein release to target area which is the small intestine. Therefore, these biodegradable materials could potentially be useful as alternative for halal capsule, instead of HPMC. Furthermore, by using these formulations, the oral delivery of protein drugs for the treatment of pediatric patients is now possible. Thus, the pain and discomfort due to frequent injections in everyday treatment can be avoided.